2018
DOI: 10.3389/fpsyt.2018.00420
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and the Consequences on Neurobiological, Psychosocial, and Somatic Conditions Across the Lifespan

Abstract: Introduction: Adverse childhood experiences (ACE) such as sexual and physical abuse or neglect are frequent in childhood and constitute a massive stressor with long-lasting adverse effects on the brain, mental and physical health.The aim of this qualitative review is to present a concise overview of the present literature on the impact of ACE on neurobiology, mental and somatic health in later adulthood.Methods: The authors reviewed the existing literature on the impact of ACE on neurobiology, mental and somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
266
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(290 citation statements)
references
References 125 publications
(146 reference statements)
14
266
2
8
Order By: Relevance
“…Markers of anxiety, such as the startle response, have been shown to be heighted in children of women reporting exposure to child abuse even after adjustment for maternal depression and the child's own trauma exposure . While the mechanisms driving these associations remain speculative, likely involving both behavioural and biological factors, the sensitivity of children to trauma is well recognised . The long‐lasting neurobiological effects of traumas during childhood may contribute to the differential associations we observe when compared to total lifetime traumatic experiences.…”
Section: Commentsupporting
confidence: 90%
“…Markers of anxiety, such as the startle response, have been shown to be heighted in children of women reporting exposure to child abuse even after adjustment for maternal depression and the child's own trauma exposure . While the mechanisms driving these associations remain speculative, likely involving both behavioural and biological factors, the sensitivity of children to trauma is well recognised . The long‐lasting neurobiological effects of traumas during childhood may contribute to the differential associations we observe when compared to total lifetime traumatic experiences.…”
Section: Commentsupporting
confidence: 90%
“…Continence requires central nervous system maturation and adequate functioning throughout the life course, including recognition and interpretation of the physical sensation to urinate, distinction between different degrees of bladder fullness and urge, planning and execution of toileting behaviors (eg, requesting permission to use a restroom), and suppression of urge until a toilet is available 46 . Consistent with the Principle of Timing and critical and sensitive periods , the consequences of ACEs may differ depending on their timing in relation to (a) development of brain regions that govern executive control, 42 (b) sensitive periods during which the central nervous system is particularly vulnerable to stressors, 42 and (c) establishment of daytime and nighttime bladder control 44 . Thus, exposure to ACEs should be assessed prenatally and during infancy, as well as during childhood and adolescence.…”
Section: Resultsmentioning
confidence: 99%
“…Previous results indicate that childhood neglect may predict deficits in the recognition of positive emotions (Young and Widom, 2014), that might explain difficulties in applying adaptive strategies, such as refocus on planning, positive reappraisal or putting a stressful life event into a more acceptable perspective. On a neurobiological level, others found that right amygdale volume mediates the association between neglect and anxiety (Roth et al, 2018) or that early exposure to either emotional or physical neglect is related to amygdala hypertrophy and mood disorders (Herzog and Schmahl, 2018). Increased risk for anxiety and mood disorders thus further reduce the capability to focus on positive outcomes in stressful live situations.…”
Section: Discussionmentioning
confidence: 99%